If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7m + -12 = -40 Reorder the terms: -12 + -7m = -40 Solving -12 + -7m = -40 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -7m = -40 + 12 Combine like terms: -12 + 12 = 0 0 + -7m = -40 + 12 -7m = -40 + 12 Combine like terms: -40 + 12 = -28 -7m = -28 Divide each side by '-7'. m = 4 Simplifying m = 4
| -2(x+8)+5=-23+x | | 7m-20=15 | | 7x+35=180 | | 72+6x=11(14x+20) | | 7m-24=-24 | | 72+6x=11(14x+50) | | -6x-19=-1 | | 8/9-4/5 | | 2/4/-1/2 | | -6(8n+14)-16n=-18n+54 | | -4x-22=6 | | -7m+11=53 | | 5X-19=-21 | | 12=x-(-2) | | -12=-6+3y | | 5/7=3/x | | -10k=20(1-10k)-20 | | -13m-16=36 | | x^7+9x^7= | | 2(16-7p)=-23-9p | | -6p-6=-36 | | 8=vf-3 | | 25=5(7x)-3 | | 15(y+3)=6(y-5) | | X^2-3x-40=o | | 10(v+2)-4v=3(2v+3)-15 | | ((8/4)6)x2 | | 5a-75=-20(a+20) | | p-2=5 | | -14x+1=-55 | | 10x+40=4x-8 | | 13x-12=4(3x+4)-4 |